Analisis Penggunaan Bahasa Indonesia Baku dalam Konteks Rumpun Biologi : Upaya Meningkatkan Keterbacaan dan Konsistensi Terminologi Ilmiah - Siregar, Maria Anastasyia; Andini, Nayani Putri; Gukguk, Nella Juriska Raja; Gaol, Reza Artha Mevia Lumban; Silaen, Wesri Martua; Febrina, Ika (Jurnal Ilmu Sosial, Humaniora dan Seni, 2024)
This study aims to analyze the use of standard Indonesian language and the consistency of scientific terminology in the context of biological sciences. Through a content analysis approach on biology practicum reports, this research identifies issues related to grammatical accuracy, sentence structure, and consistency in using scientific terms. The findings reveal several errors in the use of capital letters, punctuation, prepositions, and complex and incomplete sentence structures. Additionally, inconsistencies in writing biological terminologies were found. This study provides recommendations for terminology standardization efforts, the development of writing guidelines, and the promotion of awareness regarding the importance of consistency in using standard Indonesian language and scientific terminology in the context of biological sciences. The research findings are expected to contribute to improving the quality of scientific writing and communication in the field of biology.